Conocimientos, actitudes y prácticas acerca de la lactancia materna en puérperas ingresadas al área de gineco-obstetricia del Hospital Teófilo Dávila de agosto a noviembre 2010. - Lucas Franco, Bertha M. (2011)
According to the OMS the maternal nursing is the ideal form contributing to small children with nutrients that they need for a growth and healthy development. When we knowing the importance that this practice implies we carried out the present study that has as objective to value the knowledge, attitudes and practices about the maternal nursing in puerperal of the hospital Teófilo Dávila during august – November 2010.